Effect of varying ultrasonic duration on the dispersion of multi-walled carbon nanotubes addition to the monolithic alumina - Mohd Shuhari, Nurul Sakinah; Manshor, Hanisah; Ahmad Azhar, Ahmad Zahirani (AIP Publishing, 2024)
There is a way to improve the properties of Al2O3 which is by reinforced it with addition of Multi-Wall Carbon Nanotubes (MWCNT). However, the dispersion of MWCNT into Al2O3 will cause an agglomeration. In order to reduce the agglomeration on the mixture, the mixture was undergoes ultrasonic. In this report, the effect of addition of MWCNT into Al2O3 ceramic composite on their dispersion with various ultrasonic durations was studied. The duration of ultrasonic is varied in order to study the effect of the dispersion between them. The composition of MWCNT used was fixed at 0.5wt% for each run. The mixture was firstly dispersed into distilled water using magnetic stir for 1 hour. The mixture was ultrasonicated in ultrasonic agitation for varied time (0, 0.5, 1, 2, 3 and 4 hours) afterwards. Then, the mixture was dried in an oven at 80˚C overnight (about 12 hours) before being pressed by 2 tons load. The pressed samples were sintered at 1600 ˚C and then the properties were characterized using FESEM, density, shrinkage, and Vickers hardness. The results indicate that increasing the ultrasonic duration resulted in better dispersion and the reduction of agglomeration of MWCNT in Al2O3 matrix. 4 hours of ultrasonic duration shows the best result because it possesses high density and high hardness value. This demonstrates that the excellent dispersion of MWCNT inside Al2O3 matrix leads to the improvement of Al2O3-MWCNT properties. The excellent properties are due to the strong interfacial bonding between MWCNT and Al2O3. Thus, it can be concluded that by manipulating pressing pressure on inserts fabrication, the properties will be varied.